Ubiquitous influenza A virus in Chilean swine before the H1N1pdm09 introduction. Issue 6 (30th July 2021) - Mena, Juan; Ariyama, Naomi; Navarro, Camila; Quezada, Manuel; Brevis, Cristina; Rojas, Daniela; Medina, Rafael A.; Brito, Barbara; Ruiz, Álvaro; Neira, Victor
Abstract: Influenza A virus (IAV) was a neglected swine pathogen in South America before the 2009 H1N1 pandemic (A(H1N1)pdm2009). The A(H1N1)pdm2009 strain has widely spread among the Chilean swine population and co‐circulates with endemic H1N2 and H3N2 viruses. The presence of IAV as a swine pathogen in Chilean swine before the 2009 pandemic is unknown. To understand the IAV in swine prior to 2009, aY retrospective study of samples from pigs affected with respiratory diseases was conducted. Ninety formalin‐fixed and paraffin‐embedded lung tissues belonging to 21 intensive pig production companies located in five different administrative regions of Chile, collected between 2005 and 2008, were evaluated. The tissues were tested by immunohistochemistry (IHC), identifying that 9 out of 21 farms (42.8%) and 31 out of 90 (34.4%) samples were IAV positive. Only three out of the 31 IHC‐positive samples were positive upon RNA extraction and rtRT‐PCR analysis. Partial nucleotide sequences were obtained from one sample and characterized as an H3N2 subtype closely related to a human seasonal H3N2 IAVs that circulated globally in the mid‐90s. These results indicate that IAV was circulating in swine before 2009 and highlight the value of conducting retrospective studies through genomic strategies to analyse historical samples.